2020
DOI: 10.1007/s12663-020-01484-y
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Maxillofacial Trauma Amid COVID-19: A Comparative Study

Abstract: Introduction Pandemic caused by novel coronavirus has created an unprecedented situation of lockdown in India. This retrospective study was undertaken to evaluate the impact of COVID-19 restrictions on cases of maxillofacial trauma and its etiologic variation by comparing it with the previous year archived data. Materials and Methods Patients with maxillofacial fracture visiting during the lockdown period (Phase) were compared to the patient's record during the same time period in the year 2019 (Control). They… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 11 publications
4
39
1
4
Order By: Relevance
“…This result is in contrast to the observation by Vishal et al affirming a significant increase in maxillofacial fractures produced by assault during the COVID-19 period attributed to the depression and anxiety affecting the mental health, increasing aggression and irritability of affected people. 3 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is in contrast to the observation by Vishal et al affirming a significant increase in maxillofacial fractures produced by assault during the COVID-19 period attributed to the depression and anxiety affecting the mental health, increasing aggression and irritability of affected people. 3 …”
Section: Discussionmentioning
confidence: 99%
“…Study by Vishal et al observed a massive drop in the number of maxillofacial trauma cases due to decrease in vehicular movements during the lockdown days. 3 …”
Section: Introductionmentioning
confidence: 99%
“…Our study results showed that the number of patients admitted to ED with MFTs decreased by 43.2% during the pandemic compared to the previous year. In the literature, the rate of MFTs decreased by 80% [13][14][15][16][17][18][19]. This can be attributed to the higher time spent at home due to restrictions worldwide.…”
Section: Discussionmentioning
confidence: 99%
“…Increased domestic violence and self-destruction may contribute to the increased rates [33]. Also, a higher perceived risk to COVID-19 infection may aggravate anticipatory fear and anxiety which affects mental health and makes individuals more aggressive and irritable during the crisis [18].…”
Section: Original Articlementioning
confidence: 99%
“…Houve diminuição das ocorrências relacionadas aos traumas e complicações bucomaxilofaciais durante a pandemia pela COVID-19, assim como ocorreu em outros centros de referência para o mesmo tipo de trauma (Press, 2021;Vishal et al, 2020;Yeung, Brandsma, Karst, Smith, & Fan, 2021). Além disso as maiores reduções se relacionam com períodos de lockdown (Thiem et al, 2021).…”
Section: Discussionunclassified